COMPUTATIONAL FLUID DYNAMICS ANALYSIS OF FLOW AND COMBUSTION OF A DIESEL ENGINE - Abay, K.; Colak, U.; Yuksek, L. (YILDIZ TECHNICAL UNIV, 2018)
Efficient usage of fossil fuels and reduction of CO2 emissions are very important priorities for the automotive industry. Without increasing contributions from diesel engines and newer diesel technologies, it would not be possible to successfully meet fuel consumption and CO2 emission reduction targets. Therefore, new regulations and applications have been put into action to address exhaust gas emission problems. Some exhaust gases have become prominent with regard to strong effects, such as NOx and soot. NOx contributes to acid rain, which has deteriorating effects on the ozone layer. In this study, flow and combustion characteristics of a diesel engine are investigated by using Computational Fluid Dynamics (CFD). Whole engine components are modeled and analyses are performed for entire speed range of the engine. Calculated crank angle dependent pressure and temperature values are used as boundary condition for reactive 3D CFD simulations. Reactive CFD simulations are performed with 45 degrees sector geometry for the period that both valves are closed. In reactive simulations, RNG k-epsilon and Standard k-epsilon models are used to characterize turbulence flow field. A lagrangian approach is used for two-phase flow computations to simulate the liquid fuel injection. Commercially available CFD code called Forte Reaction Design and its sub-module Chemkin are used for three dimensional reactive simulations, moving grid generation and problem setup. Predicted in-cylinder pressure and apparent heat release rate are validated with experimental results. NOx and Soot formations as a result of combustion process are also investigated. Optimum level of NO,, and Soot formation obtained with 8.5% EGR usage.
Keywords: Diesel Engine; Computational Fluid Dynamics; Exhaust Gas Recirculation; NOx; Soot; EMISSIONS; KINETICS; Thermodynamics